Quantum simulation of interaction blockade in a two-site Bose–Hubbard system with solid quadrupolar crystal. (20th May 2015) - Nie, Xinfang; Li, Jun; Cui, Jiangyu; Luo, Zhihuang; Huang, Jiahao; Chen, Hongwei; Lee, Chaohong; Peng, Xinhua; Du, Jiangfeng
Abstract: The Bose–Hubbard model provides an excellent platform for exploring exotic quantum coherence. Interaction blockade is an important fundamental phenomenon in the two-site Bose–Hubbard system (BHS), which gives a full quantum description for the atomic Bose–Josephson junction. Using the analogy between the two-site BHS and the quadrupolar nuclear magnetic resonance (NMR) crystal, we experimentally simulate a two-site Bose–Hubbard system in a NMR quantum simulator composed of the quadrupolar spin-3/2 sodium nuclei of a NaNO3 single crystal, and observe the interesting phenomenon of interaction blockade via adiabatic dynamics control. To our best knowledge, this is the first experimental implementation of the quantum simulation of the interaction blockade using quadrupolar nuclear system. Our work exhibits important applications of quadrupolar NMR in the quantum information science, i.e. a spin-3/2 system can be used as a full 2-qubit su(4) system, if the quadrupole moment is not fully averaged out by fast tumbling in the liquid phase.